New Proposals for a Quality Education in Chile: The Acciona Program and its Scope - Carmen Gloria Burgos-Videla (Revista Electrónica Educare)
This research is a diagnosis generated from the document analysis of reports issued by the cultural council regarding the results obtained with the implementation of the Acciona program (2011-2013). This program is promoted throughout the Chilean territory with the aim of improving the quality of education through the development of creativity, cultural and artistic training, and the development of the students’ socio-emotional abilities. The analysis criteria include consistency, coverage, and timing. The main results of the diagnosis are that government initiatives and programs to improve the quality of education do not consider appropriateness. It is inferred that evaluation is superficial and general. Findings indicate that a creative education should start by training teachers and by implementing programs that procedurally assess progress at all levels taught, but by keeping a common goal –human development in its full creative expression. Additionally, we believe that educational policies should change the technological approach for a critical-practical approach to include curricular programs such as Acciona.